(untitled) (Environmental Smoke, 2021)
The Miño River is a good example of bedrock rivers, where sediment geochemistry is scarcely studied. Its urban reach when passing through the city of Ourense gathers some characteristics that provide interest to its sediments, like scarcity of fine sediments accumulation and the impact of several human activities. Sediments trapped by potholes and other rock cavities were considered. In order to evaluate society-nature interactions through sediment composition it is critical to determine the compositional background (in absence of human alterations), particularly when working with trace elements. This work presents an exploratory assay to determine background in sediments from bedrock rivers by using two uncommon elements, uranium (U) and thorium (Th). To determine their background different statistical techniques were applied in order to set the background composition value and calculate possible enrichments. Background was calculated by simple least squares lineal regression by using Al as independent variable (reference element) resulting in 8.7 mgU kg-1 and 5.6 mgTh kg-1. Enrichments were found in some particular samples and can be attributed to intrinsic microenvironment complexities inside rock cavities.